2023
DOI: 10.3390/pathogens12040623
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infections: The Current Scenario and Future Prospects

Abstract: Urinary tract infections (UTIs) are among the most common bacterial infections worldwide, occurring in both community and healthcare settings. Although the clinical symptoms of UTIs are heterogeneous and range from uncomplicated (uUTIs) to complicated (cUTIs), most UTIs are usually treated empirically. Bacteria are the main causative agents of these infections, although more rarely, other microorganisms, such as fungi and some viruses, have been reported to be responsible for UTIs. Uropathogenic Escherichia co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(56 citation statements)
references
References 112 publications
1
53
1
1
Order By: Relevance
“…The risk factors identi ed in the study, including female gender, prolonged Foley's catheterization, and urinary tract abnormalities, are well-established in the literature. [10,12,[16][17][18][19]27] These ndings emphasize the importance of identifying and closely monitoring high-risk patients to mitigate the risk of UTI development. Targeted preventive strategies, such as judicious use of catheterization, timely removal of urinary catheters, and prompt management of urinary tract abnormalities, may aid in reducing the burden of UTIs in this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors identi ed in the study, including female gender, prolonged Foley's catheterization, and urinary tract abnormalities, are well-established in the literature. [10,12,[16][17][18][19]27] These ndings emphasize the importance of identifying and closely monitoring high-risk patients to mitigate the risk of UTI development. Targeted preventive strategies, such as judicious use of catheterization, timely removal of urinary catheters, and prompt management of urinary tract abnormalities, may aid in reducing the burden of UTIs in this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect infection can also occur through colonisation of the urinary or gastrointestinal tracts. Endogenous infections can also result from translocation through the epithelium of the GI tract [ 97 , 98 , 99 , 100 , 102 , 103 ] ( Figure 3 ).…”
Section: Causes Of E Faecalis Bacteraemiamentioning
confidence: 99%
“…A UTI may also progress to further complications: increasing the risk of urinary calculi development, UI, chronic prostatitis and affecting the upper urinary tract (pyelonephritis, kidney abscess, kidney failure) [36,37]. The pathophysiology of infectious UTI is beyond the scope of this review and can be found in some papers in this field [38][39][40]. However, UTI development may also result from the patient's pharmacotherapy.…”
Section: Urinary Tract Infectionsmentioning
confidence: 99%